1979
DOI: 10.1159/000241173
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Pattern of Autonomic Heart Rate Control during Hypoxia in Fetal and Newborn Lambs

Abstract: Autonomic nervous control of heart rate (HR) during hypoxia was studied longitudinally using 9 chronically catheterized fetal lambs (109 day to term) and 10 newborn lambs (2–28 days old). Changes in heart rate (ΔHR) during hypoxia were age-dependent. Before 120 days of gestation ΔHR was insignificant, but between 120 days to term bradycardia occurred. The newborn response was marked tachycardia. Autonomic influences on HR were quantified using atropine and propranolol blockade. In fetal lambs, antagonistic inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 10 publications
5
26
0
Order By: Relevance
“…Akagi et al (30) also demonstrated that maternal and fetal hypoxemia could be induced in sheep at 125 dGA by reducing maternal inspired O 2 content without inducing hypertension. Several studies have shown that late in gestation, fetal hypoxemia does elevate fetal blood pressure (23,24,26,27,36). In our study, hypertension supervened after hypoxemia in the DM-treated but not control fetuses at 105 dGA, producing the response characteristic of a more mature fetus.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Akagi et al (30) also demonstrated that maternal and fetal hypoxemia could be induced in sheep at 125 dGA by reducing maternal inspired O 2 content without inducing hypertension. Several studies have shown that late in gestation, fetal hypoxemia does elevate fetal blood pressure (23,24,26,27,36). In our study, hypertension supervened after hypoxemia in the DM-treated but not control fetuses at 105 dGA, producing the response characteristic of a more mature fetus.…”
Section: Discussionsupporting
confidence: 44%
“…However, relatively little is known about fetal responses to acute hypoxemia before 120 dGA. Cardiovascular responses of fetal sheep to hypoxemia before 100 dGA are different from those of fetal sheep at Ͼ100 dGA (26,27). In addition, gestational changes in organ blood flow (28) and neurohormonal regulation (29) suggest that the responses to acute hypoxemia in fetuses Ͻ120 dGA would be different from those Ͼ120 dGA.…”
mentioning
confidence: 99%
“…Release of epinephrine (E) into the fetal circulation opposes vagal tone and returns FHR to basal levels (10). The fetal peripheral vasoconstriction is maintained by increased release of vasoactive agents into the fetal circulation, such as catecholamines, neuropeptide Y (NPY), and AVP (1,8,20,27,50,51,55,56,59).Although the cardiovascular responses to acute hypoxemia or asphyxia are known to change between mid and late gestation (7,30,33,34,64,65), no study has investigated developmental changes in cardiovascular responses to hy- …”
mentioning
confidence: 99%
“…Although the cardiovascular responses to acute hypoxemia or asphyxia are known to change between mid and late gestation (7,30,33,34,64,65), no study has investigated developmental changes in cardiovascular responses to hy-…”
mentioning
confidence: 99%
See 1 more Smart Citation